Increasing atmospheric CO2 reduces metabolic and physiological differences between isoprene‐ and non‐isoprene‐emitting poplars. Issue 2 (4th July 2013) - Way, Danielle A.; Ghirardo, Andrea; Kanawati, Basem; Esperschütz, Jürgen; Monson, Russell K.; Jackson, Robert B.; Schmitt‐Kopplin, Philippe; Schnitzler, Jörg‐Peter
Summary: Isoprene, a volatile organic compound produced by some plant species, enhances abiotic stress tolerance under current atmospheric CO2 concentrations, but its biosynthesis is negatively correlated with CO2 concentrations. We hypothesized that losing the capacity to produce isoprene would require stronger up‐regulation of other stress tolerance mechanisms at low CO2 than at higher CO2 concentrations. We compared metabolite profiles and physiological performance in poplars ( Populus × canescens ) with either wild‐type or RNAi‐suppressed isoprene emission capacity grown at pre‐industrial low, current atmospheric, and future high CO2 concentrations (190, 390 and 590 ppm CO2, respectively). Suppression of isoprene biosynthesis led to significant rearrangement of the leaf metabolome, increasing stress tolerance responses such as xanthophyll cycle pigment de‐epoxidation and antioxidant levels, as well as altering lipid, carbon and nitrogen metabolism. Metabolic and physiological differences between isoprene‐emitting and suppressed lines diminished as growth CO2 concentrations rose. The CO2 dependence of our results indicates that the effects of isoprene biosynthesis are strongest at pre‐industrial CO2 concentrations. Rising CO2 may reduce the beneficial effects of biogenic isoprene emission, with implications for species competition. This has potential consequences for future climate warming, as isoprene emitted from vegetation has strong effects on global atmospheric chemistry.